2016
DOI: 10.1371/journal.pone.0147108
|View full text |Cite
|
Sign up to set email alerts
|

Focus on Quality: Investigating Residents’ Learning Climate Perceptions

Abstract: BackgroundA department’s learning climate is known to contribute to the quality of postgraduate medical education and, as such, to the quality of patient care provided by residents. However, it is unclear how the learning climate is perceived over time.ObjectivesThis study investigated whether the learning climate perceptions of residents changed over time.MethodsThe context for this study was residency training in the Netherlands. Between January 2012 and December 2014, residents from 223 training programs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 28 publications
0
17
1
3
Order By: Relevance
“…Moreover, research on data of 7 cohorts of medical students showed that differences between cohorts explained only 0.01% of the variance in multiple choice examination results, compared to 83% for the differences between subjects within cohorts, and 12% for random error [22]. Similarly, research among residents showed that repeated learning environment assessments by different groups of residents for quality assurance and improvement purposes did not show any meaningful changes in overall scores over time [8]. Third, leaving residents' SPEED scores could have been affected by social desirability bias, if these residents desired to stay at or return to the same department later in their career.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, research on data of 7 cohorts of medical students showed that differences between cohorts explained only 0.01% of the variance in multiple choice examination results, compared to 83% for the differences between subjects within cohorts, and 12% for random error [22]. Similarly, research among residents showed that repeated learning environment assessments by different groups of residents for quality assurance and improvement purposes did not show any meaningful changes in overall scores over time [8]. Third, leaving residents' SPEED scores could have been affected by social desirability bias, if these residents desired to stay at or return to the same department later in their career.…”
Section: Discussionmentioning
confidence: 99%
“…show any meaningful changes in overall scores over time. (8) Third, leaving residents' SPEED scores could have been affected by social desirability bias, if these residents desired to stay at or return to the same department later in their career. However, it is unlikely that this would apply to all leaving residents.…”
Section: Discussionmentioning
confidence: 99%
“…(22) Similarly, research among residents showed that repeated learning environment assessments by different groups of residents for quality assurance and improvement purposes did not show any meaningful changes in overall scores over time. (8) Third, leaving residents' SPEED scores could have been affected by social desirability bias, if these residents desired to stay at or return to the same department later in their career. However, it is unlikely that this would apply to all leaving residents.…”
Section: Discussionmentioning
confidence: 99%
“…7As a result, a healthy learning environment may not only support the professional development of residents but also improve the quality of the patient care they provide. 8The learning environment has been described as the formal and informal context in which learning takes place, (8) comprising the content, atmosphere and organization of the education program. (2,9) The Scan of Postgraduate Education Environment Domains (SPEED) was developed and validated as a concise instrument, based on a solid theoretical framework,(2) to capture residents' perceptions of these three domains of PGME programs.…”
Section: Introductionmentioning
confidence: 99%